2020
DOI: 10.1103/physreva.102.062810
|View full text |Cite
|
Sign up to set email alerts
|

Rovibrational quenching of C2 anions in collisions with He, Ne, and Ar atoms

Abstract: The molecular anion C 2 − is currently of interest as a candidate for laser cooling due to its electronic structure and favorable branching ratios to the ground electronic and vibrational states. Helium has been proposed as a buffer gas to cool the molecule's internal motion. We calculate the cross sections and corresponding rates for rovibrational inelastic collisions of C 2 − with He, and also with Ne and Ar, on three-dimensional ab initio potential energy surfaces using quantum scattering theory. The rates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…5 are indeed similar to those which we have obtained earlier for the C − 2 anion colliding with the He, Ne, and Ar set of systems that we have recently studied. 21 For both the anions, we have found that the vibrational quenching cross sections with He are uniformly very small, while we also found that they increase by orders of magnitude when the larger and more polarizable Ar atom becomes the collisional partner for either of these anionic molecules. Although such general behavior could be reasonably expected from what we know in these systems about their interaction forces, it is nevertheless reassuring to obtain quantitative confirmation on the extent of the size differences from detailed, and in principle exact, scattering calculations.…”
Section: Vibrationally Inelastic Cross Sections and Rate Coefficientsmentioning
confidence: 57%
See 2 more Smart Citations
“…5 are indeed similar to those which we have obtained earlier for the C − 2 anion colliding with the He, Ne, and Ar set of systems that we have recently studied. 21 For both the anions, we have found that the vibrational quenching cross sections with He are uniformly very small, while we also found that they increase by orders of magnitude when the larger and more polarizable Ar atom becomes the collisional partner for either of these anionic molecules. Although such general behavior could be reasonably expected from what we know in these systems about their interaction forces, it is nevertheless reassuring to obtain quantitative confirmation on the extent of the size differences from detailed, and in principle exact, scattering calculations.…”
Section: Vibrationally Inelastic Cross Sections and Rate Coefficientsmentioning
confidence: 57%
“…The PESs for CN − /He and CN − /Ar can be compared to similar systems such as C − 2 /He and C − 2 /Ar that we have recently investigated. 21 The location of the minimum interaction energy for both anions interacting with He and Ar, respectively, is very similar with the main difference being the perpendicular angle of the well for C − 2 . The off-diagonal matrix elements for these systems are also similar in magnitude and range, but being slightly larger for the interaction of He and Ar with C − 2 , explaining the larger quenching rates for this anion (see below).…”
Section: Cn − Potential Energy Curve and Dipole Momentmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the fairly large rotationally inelastic rate coefficients obtained here for the C − 2 /p.H 2 (j = 0) system collisions, and the clearly efficient thermalisation modelling we have presented, suggest that it is worth considering molecular hydrogen as a possible buffer gas to also quench the internal vibrational motion of C − 2 , a result providing an important prerequisite for subsequent laser cooling experiments and simulations. We have already shown, in fact, that for the case of Ar as a buffer gas partner, the vibrational quenching rate constants for ν = 2 and ν = 1 are of reasonable magnitude [33]to be of interest in cold ion trap studies. However, and as discussed earlier in the present study, Ar can only be used down to around 50 K, which would be a significant limitation for cold ion studies.…”
Section: Discussionmentioning
confidence: 94%
“…Our simulations showed that thermalisation times of the rotational states of C − 2 with noble gases decreased in the order helium > neon > argon, due to the increasing interaction energy with atomic size and with dipole polarisability which are then yielding larger rate coefficients [31,32]. We have also calculated the rate coefficients for vibrationally inelastic collisional quenching of the anion's ν = 2 and ν = 1 levels [33], a step which can be useful in laser cooling experiments. As C − 2 has no oscillating dipole, the vibrational levels are long lived with the ground electronic state's v = 2 levels persisting for over five seconds [13].…”
Section: Introductionmentioning
confidence: 84%